Dual RNA-Seq Analysis of the Pine-Fusarium circinatum Interaction in Resistant (Pinus tecunumanii) and Susceptible (Pinus patula) Hosts - Erik A. Visser; Jill L. Wegrzyn; Emma T. Steenkamp; Alexander A. Myburg; Sanushka Naidoo (Microorganisms, 2019)
Fusarium circinatum poses a serious threat to many pine species in both commercial and natural pine forests. Knowledge regarding the molecular basis of pine-F. circinatum host-pathogen interactions could assist efforts to produce more resistant planting stock. This study aimed to identify molecular responses underlying resistance against F. circinatum. A dual RNA-seq approach was used to investigate host and pathogen expression in F. circinatum challenged Pinus tecunumanii (resistant) and Pinus patula (susceptible), at three- and seven-days post inoculation. RNA-seq reads were mapped to combined host-pathogen references for both pine species to identify differentially expressed genes (DEGs). F. circinatum genes expressed during infection showed decreased ergosterol biosynthesis in P. tecunumanii relative to P. patula. For P. tecunumanii, enriched gene ontologies and DEGs indicated roles for auxin-, ethylene-, jasmonate- and salicylate-mediated phytohormone signalling. Correspondingly, key phytohormone signaling components were down-regulated in P. patula. Key F. circinatum ergosterol biosynthesis genes were expressed at lower levels during infection of the resistant relative to the susceptible host. This study further suggests that coordination of phytohormone signaling is required for F. circinatum resistance in P. tecunumanii, while a comparatively delayed response and impaired phytohormone signaling contributes to susceptibility in P. patula.